Sugarcane Nutrient Management Using Leaf Analysis - J. Mabry McCray; Rao Mylavarapu (EDIS, 2010)
SS-AGR-335, a 7-page illustrated fact sheet by J. Mabry McCray and Rao Mylavarapu, provides growers with sufficiency categories of leaf nutrient concentrations and nutrient management suggestions for each category. Includes references. Published by the UF Department of Agronomy, July 2010.